2017
DOI: 10.2134/jeq2016.08.0316
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Changes in Cadmium Speciation in Brazilian Soils Evaluated Using Cd LIII–Edge XANES and Chemical Fractionation

Abstract: Chemical speciation of soil cadmium (Cd) dictates its mobility and potential toxicity in the environment. Our objective was to compare temporal changes in speciation of Cd(II) reacted with samples from six Brazilian soils having varying Cd(II) sorption capacities. Cadmium L-edge X-ray absorption near edge structure (XANES) analysis showed there were short-term changes in speciation after reaction with 4.45 mmol Cd kg for 0.5 and 6 h. Chemical fractionation evaluated changes in Cd extractability after reaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 48 publications
(73 reference statements)
1
9
0
Order By: Relevance
“…However, Cd was associated with either the F2, reducible fraction (47PC = 99% and 5AP = 83%) or the F4, residual fraction (35PC = 100%). Colzato et al (2017) observed similar result in a Brazilian Typic Argiudoll which had 75% of Cd extracted by 0.5 mol L -1 NH 2 OH.HCl.…”
Section: Sequential Extractionsupporting
confidence: 69%
“…However, Cd was associated with either the F2, reducible fraction (47PC = 99% and 5AP = 83%) or the F4, residual fraction (35PC = 100%). Colzato et al (2017) observed similar result in a Brazilian Typic Argiudoll which had 75% of Cd extracted by 0.5 mol L -1 NH 2 OH.HCl.…”
Section: Sequential Extractionsupporting
confidence: 69%
“…Colzato et al (2017) studied short‐term temporal changes in Cd speciation and long‐term changes in Cd extractability in relation to the properties of highly weathered Brazilian Oxisols and less weathered Mollisols and Entisols. Cadmium L‐edge XANES showed that Cd was mainly sequestered as Cd bound to organic matter and to Fe and Al oxides (or montmorillonite in the smectite‐rich soil sample).…”
Section: Summaries Of Papers In This Special Sectionmentioning
confidence: 99%
“…Their work showed that although the short-term reactions of nanomaterials are dependent on the Cu form and soil chemistry (e.g., pH), in the long term, irrespective of their original form, all of the examined forms of Cu nanoparticles transformed into Cu bound to iron oxyhydroxide or natural organic matter. Colzato et al (2017) studied short-term temporal changes in Cd speciation and long-term changes in Cd extractability in relation to the properties of highly weathered Brazilian Oxisols and less weathered Mollisols and Entisols. Cadmium L-edge XANES showed that Cd was mainly sequestered as Cd bound to organic matter and to Fe and Al oxides (or montmorillonite in the smectite-rich soil sample).…”
Section: Fate and Bioavailability Of Contaminants In Soilsmentioning
confidence: 99%
“…Fitting was conducted using two approaches. The first was performed as described by Colzato et al (2017) and consisted in fitting all possible combinations of 12 standards with a maximum of four standards per fit in all soil samples selected for XANES analysis. In this procedure no energy shift was used to identify the standards present in the fits with the lowest residual, considered the best fits.…”
Section: Linear Combination Fitting (Lcf)mentioning
confidence: 99%
“…One of the main concerns on using LCF approach is the selection of the reference compounds to perform LCF. Previous authors used different methods to model S XANES spectra to eliminate the necessity of previous assumptions about the composition of the sample, such as principal component analysis -PCA (Beauchemin et al, 2002) and use of aqueous diluted samples (Almkvist et al, 2010) We used two approaches as described by Colzato et al (2017) and to select the reference compounds to perform the fit. All fits were set to be performed by a combination of a maximum of four reference compounds, and only factions greater than 0.1 (10%) were considered.…”
Section: 4mentioning
confidence: 99%